Adjacency relations induced by some Alexandroff topologies on Zn - Sang-Eon Han (AIMS Mathematics, 2022)
Let $ (X, T) $ be an Alexandroff space. We define the adjacency relation $ AR_T $ on $ X $ induced by $ T $ as the irreflexive relation defined for $ x ≠ y $ in $ X $ by: